Penerapan Tutor Sebaya pada Esktrakurikuler Tari Pasambahan Kreasi di SMP Negeri 25 Padang - Uswatun Hasanah; Susmiarti Susmiarti (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This study aims to find out how the results of extracurricular dance pasambahan creations using the peer tutor method at SMP Negeri 25 Padang. This type of research is qualitative research using a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The data in this study uses secondary data and primary data. Data were collected through literature studies, observations, interviews and documentation. The steps to analyze the data are data reduction, data display and conclusion. The results of the study show that the application of the peer tutor method in dance extracurricular arts at SMP Negeri 25 Padang has improved the ability of students to understand 3 basic elements of dance, namely wiraga, wirama, and wirasa. This is evident from the observation results, from the first meeting to the last meeting. There has been an increase in the ability of students to make movements, adjust movements with musical accompaniment, and a sense has arisen when students make movements.